The stranger game : a novel - Gadol, Peter (Hanover Square Press, 2018)
"Rebecca's on-again, off-again boyfriend, Ezra, has gone missing, but when she notifies the police, they seem surprisingly unconcerned. They suspect he has been playing the "stranger game," a viral hit in which players start following others in real life, as they might otherwise do on social media. As the game spreads, however, the rules begin to change, play grows more intense and disappearances are reported across the country. Curious about this popular new obsession, and hoping that she might be able to track down Ezra, Rebecca tries the game for herself. She also meets Carey, who is willing to take the game further than she imagined possible. As her relationship with Carey and involvement in the game deepen, she begins to uncover an unsettling subculture that has infiltrated the world around her"--